Upgrading Juru Pemantau Jentik dan Pemanfaatan Kontainer Tertutup untuk Meningkatkan Angka Bebas Jentik di Wilayah Puskesmas Sukawati II Gianyar - I Wayan Sudiadnyana (Poltekkes Kemenkes Denpasar, 2020)
Dengue fever is still a health problem in the province of Bali including in Gianyar Regency. In the area of Sukawati II Health Center, during 2017 there were 30 cases of DHF with larva index of around 80.2%. Efforts to control mosquito populations are needed by involving the community through vector control activities. The aim of community service is to train larva monitoring persons (jumantik) as a motivator for community participation in the prevention of DHF. The activities were carried out in several stages, namely: socialization, jumantik training, giving closed containers and larvae surveys. The results of community service have been carried out counseling to 34 jumantik and the delivery of 60 closed containers in the territory of Singapadu Village, Gianyar. The larva index in the Singapadu Village area before upgrading was 86.3% and after upgrading was 90.9% or an increase of 4.6%. Jumantik which has been promoted to continue to strive to increase community participation by conducting vector control activities once a week.Keywords: Upgrading, larva monitoring persons (Jumantik)